Economic Consequences of Harmful Algal Blooms: Literature Summary - Sherry L. Larkin; Charles M. Adams (EDIS)
This 10-page fact sheet summarizes the existing literature that attempts to measure some of the economic consequences associated with harmful algal blooms and describes the methodologies, types and sources of data used, types of HABS examined, research gaps in previous studies. Was written by Sherry L. Larkin and Charles M. Adams, and published by the UF Department of Food and Resource Economics, August 2013. http://edis.ifas.ufl.edu/fe936